Impact of increased visceral adiposity with normal weight on the progression of arterial stiffness in Japanese patients with type 2 diabetes. Issue 1 (10th March 2015) - Bouchi, Ryotaro; Minami, Isao; Ohara, Norihiko; Nakano, Yujiro; Nishitani, Rie; Murakami, Masanori; Takeuchi, Takato; Akihisa, Momoko; Fukuda, Tatsuya; Fujita, Masamichi; Yoshimoto, Takanobu; Ogawa, Yoshihiro
Abstract : Objective: Normal-weight abdominal obesity has been reported to be associated with poor mortality. We aimed to investigate the impact of increased visceral adiposity with normal weight (OB(−)VA(+)) on the progression of arterial stiffness in patients with type 2 diabetes. Methods: This was a cross-sectional study of 414 patients with type 2 diabetes (mean age 64±12 years; 40.3% female). Visceral fat area (VFA, cm 2 ) was measured by a dual bioelectrical impedance analyzer. Arterial stiffness was assessed by brachial-ankle pulse wave velocity (baPWV, cm/s). Patients were divided into four groups by VFA and body mass index (BMI, kg/m 2 ) as the following: BMI<25 kg/m 2 and VFA<100 cm 2 (obesity (OB)(−)visceral adiposity (VA)(−)), BMI≥25 kg/m 2 and VFA<100 cm 2 (OB(+)VA(−)), BMI<25 kg/m 2 and VFA≥100 cm 2 (OB(−)VA(+)), and BMI≥25 kg/m 2 and VFA≥100 cm 2 (OB(+)VA(+)). Multivariate linear regression analysis was done to determine the impact of OB(−)VA(+) on arterial stiffness. Results: Among the patients, 7.2% were OB(−)VA(+) with higher baPWV levels (1956±444 cm/s) than those with OB(+)VA(−) (1671±416 cm/s, p=0.014), those with OB(+)VA(+) (1744±317 cm/s, p=0.048), and those with OB(−)VA(−) (1620±397 cm/s, p=0.024). In multivariate linear regression analysis, OB(−)VA(+) remained independently associated with baPWV (standardized β 0.184, p=0.001). Conclusions: This study provides evidence for the burden of arterial stiffness in OB(−)VA(+) patients with type 2 diabetes; therefore, evaluation of visceral adiposity is of clinical relevance for the better management of non-obese individuals as well as obese populations.